Limitations of Islamic Religious Education in Muslim Minority Settings: A Case Study of Nagori Tongah Village, Simalungun Regency - Muhammad Iqbal; Muhammad Fajar; Minanda Ndrey Faza Brata; Muhammad Aziz; Muhammad Luthfi Ma'sum; Muhammad Abror Firdaus; Batubara, M. Syavriaji Aqila (As-sunnah: Jurnal Pengabdian Masyarakat, 2025)
Islamic Religious Education (IRE) plays a vital role in shaping students’ moral values and Islamic identity. However, its implementation in Muslim minority contexts is constrained by structural, social, and cultural challenges. This qualitative case study explores the limitations of IRE and identifies adaptive strategies in Nagori Tongah Village, Simalungun Regency, North Sumatra, Indonesia. Data were collected through in-depth interviews, observations, and document analysis involving IRE teachers, school principals, Muslim community leaders, and parents, and were analyzed using Miles and Huberman’s interactive model with triangulation. The findings indicate that IRE in Muslim minority settings faces limitations including a shortage of qualified teachers, inadequate facilities, weak institutional and policy support, and strong socio-cultural influences from non-Muslim environments. These constraints hinder the effective internalization of Islamic values, which remains largely cognitive rather than practical. The study highlights the urgency of contextual and collaborative educational approaches grounded in multicultural principles to strengthen IRE in Muslim minority areas. This research contributes to the development of inclusive and sustainable Islamic Religious Education policies and practices in minority contexts.